A summing up: Synthesis 2007: Changing the way we manage water for food, livelihoods, health and the environment - Harrington, Larry W.; Humphreys, E.; Huber-Lee, Annette; Nguyen-Khoa, Sophie; Cook, Simon E.; Gichuki, Francis N.; Johnson, Nancy L.; Ringler, Claudia; Geheb, Kim; Woolley, Jonathan N. (CGIAR Challenge Program on Water and Food, 2008)
This reports summarizes and synthesizes activities and achievements of the CGIAR Challenge Program on Water and Food (CPWF) through the end of 2007. The CPWF is an intiative of the CGIAR designed to take on the global challenge of water scarcity and food security. It is an international, multi-institutional researchfor- development initiative that brings together scientists, development specialists and river basin communities, and seeks to create and disseminate international public goods (IPGs) helpful in achieving food security, reducing poverty, improving livelihoods, reducing agriculture–related pollution, and enhancing environmental security. The CPWF conducts its research on water and food in nine ‘benchmark’ river basins, organized around five different themes. This work is being implemented through competitive-call projects, Basin Focal Projects (BFPs), small grant projects and synthesis research. This report is one example of the latter. Projects and outputs Part of the CPWF’s work has focused on increasing water productivity in rainfed environments. Achievements include the further development of conservation agriculture for no-till sowing into crop residues; “slash and mulch” to replace “slash and burn” practices in hillside agriculture; water harvesting systems for dryland locations; understanding livelihood vulnerability and farmers’ coping strategies; and developing and encouraging the distribution—through community ‘participatory’ varietal selection and seed schemes—of drought-tolerant sorghum, wheat, and other crops. Progress has also been made in increasing water productivity in irrigated and salt-affected environments, especially where water is scarce and there are opportunities to increase its productivity. Examples include the development and testing of salt-tolerant germplasm for rice and other crops to make more effective use of salt-affected areas; understanding how to use wastewater in irrigated peri-urban agriculture to produce safe and nutritious vegetables; and developing aerobic rice germplasm and management practices to produce more rice with less water.